Problems of middle ear and hearing in cleft children - Sharma, Ramesh Kumar (Medknow Publications, 2009)
The hearing loss in a cleft patient is a well known complication, but generally gets ignored. These children continue to have recurrent otitis media with effusion that affects the hearing abilities. Unfortunatley the middle ear function may not improve with palatoplasty.Cleft palate teams need to follow up all such children beginning at birth and going into adulthood, decades after a ‘successful’ palate repair. These patients should have careful otological and audiological surveillance with appropriate interventions whenever required. The review article discusses the current status of hearing management in patients with cleft palate.